A solution-based copper-indium-gallium-sulfur thin film solar cell module based on ultraviolet-green light collaborative scribing and a preparation method thereof

CN122909903APending Publication Date: 2026-10-13NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611105395.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

常规机械P3存在明显不足:刀尖宽度远大于激光聚焦光斑,划线沟道宽(60~80 μm);同时,为避免刀具振动损伤邻侧的P2互连通道,P3必须与P2保持较大安全间距

Benefits of technology

[0029]1、本发明采用355 nm紫外激光完成P1和P2划线,可有效降低划线过程中的热损伤,提高背电极隔离质量及子电池互连质量;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909903A_ABST
    Figure CN122909903A_ABST
Patent Text Reader

Abstract

The application discloses a solution method copper indium gallium sulfide thin film solar cell module based on ultraviolet-green light cooperative scribing and a preparation method thereof. The module adopts a multilayer film system structure of sodium-calcium glass, a molybdenum back electrode, a copper indium gallium sulfide absorption layer, a cadmium sulfide buffer layer, an intrinsic zinc oxide high-resistance window layer and a low-resistance conductive window layer, and realizes monolithic series integration of sub-cells through three scribing procedures. P1 and P2 adopt 355 nm ultraviolet laser, and the scribing channel with low damage and high isolation is obtained on the solution method copper indium gallium sulfide absorption layer with relatively low thermal stability by using the characteristics of high photon energy and small thermal diffusion of the ultraviolet laser; P3 adopts 532 nm green light laser to replace the past mechanical scribing mode, and the six-section series module prepared on a 10.5 cm2 aperture area by the method realizes photoelectric conversion efficiency of 6.52% and open circuit voltage of 5.18 V. The application provides a process path with low thermal damage and high spatial precision for the modular integration of the solution method chalcopyrite thin film solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of modular integration technology of thin-film solar cells, specifically to a solution-based copper indium gallium sulfide thin-film solar cell module based on ultraviolet-green light synergistic tracing and its preparation method. Background Technology

[0002] With the increasing prominence of the global energy crisis and environmental problems, the development and utilization of clean and renewable energy has become a common strategic choice for countries around the world. Among many renewable energy sources, solar energy is widely recognized as one of the most promising clean energy sources due to its natural advantages such as wide distribution, inexhaustibility, and sustainability. Currently, silicon-based solar cells occupy a very high market share in the photovoltaic market due to their first-mover advantage and mature industrial chain. However, silicon-based cells have inherent limitations: crystalline silicon is an indirect bandgap material with a low light absorption coefficient, requiring a thickness of hundreds of micrometers, resulting in high material consumption; moreover, the purification of high-purity silicon materials is energy-intensive, and the modules are brittle and hard, making them difficult to be flexible, which limits their application in emerging scenarios such as building-integrated photovoltaics and wearable devices. Therefore, developing compound thin-film solar cells represented by copper indium gallium selenide (CIGSe), utilizing its advantages such as direct bandgap and high light absorption coefficient, is an important path to overcome the bottlenecks of silicon-based technology.

[0003] Copper indium gallium selenide (CIGSe) thin-film solar cells have become one of the most commercially successful compound thin-film solar cells due to their extremely high light absorption coefficient, flexible fabrication, and good radiation resistance. The highest laboratory conversion efficiency has exceeded 23%, and the module efficiency has surpassed 20%. However, with the expansion of the industry, raw material costs will continue to rise, becoming a key bottleneck restricting its further large-scale adoption. To address this, researchers have attempted to partially replace selenium (Se) with sulfur (S) to form copper indium gallium sulfide selenide (CIGS) quaternaries, aiming to further improve device performance and expand the application scenarios of tandem cells. Currently, the mainstream vacuum preparation methods for CIGS (co-evaporation and sputtering followed by selenization) have significant limitations: the chemical ratios of each element are extremely difficult to control precisely during multi-source co-evaporation, resulting in a narrow process window and low yield; vacuum equipment requires large investments and has low raw material utilization, making it difficult to leverage low-cost advantages; and as the substrate area increases, the problems of uneven film thickness and compositional deviation worsen dramatically, failing to meet the requirements of large-area modules for consistent sub-cell performance. This is the key technical motivation for adopting the solution-based approach in this invention.

[0004] In recent years, significant progress has been made in the research of preparing chalcopyrite-type light-absorbing layers using solution methods as an alternative to vacuum methods. Solution methods utilize molecular precursors such as metal salts (thiourea) to form films under ambient pressure through spin-coating or coating, followed by rapid thermal annealing and sulfurization to achieve crystallization. This eliminates the dependence on expensive vacuum equipment, resulting in high raw material utilization and representing a feasible route to reduce the manufacturing cost of chalcopyrite thin-film solar cells. In sulfur-rich CIGS systems, solution methods have achieved conversion efficiencies exceeding 11% for single-cell small-area devices, with an open-circuit voltage of approximately 0.87 V, demonstrating promising application prospects.

[0005] For thin-film solar cells to move from small-area laboratory devices to practical products, a core engineering problem must be solved: how to integrate multiple sub-cells in series on a limited substrate area. Monolithic integration—that is, completing the series interconnection of sub-cells on the same substrate through selective scribing and thin-film deposition—has become the standard module architecture for vacuum-processed thin-film photovoltaic products such as copper indium gallium selenide (CIGS) and cadmium telluride (CdTe) due to its compact structure, lack of external lead bonding, and high long-term reliability. Its basic process includes three scribing steps: P1 cuts the back electrode layer to define the sub-cell unit; P2 establishes a vertical interconnection channel between the front electrode and the back electrode of the adjacent sub-cell; and P3 cuts the front electrode to force current to flow along the series path. The spatial layout accuracy and channel quality of the three scribing steps directly determine the photoelectric conversion efficiency loss (CTM loss) of the module. When applying the monolithic integration scribing process to solution-processed CIGS light-absorbing layers, a challenge arises: solution-processed CIGS thin films have richer grain boundaries and may contain residual carbon / oxygen impurities within the grains, resulting in lower intrinsic thermal stability compared to materials deposited at high temperatures in vacuum. This is reflected in the electrical performance of the components as a decrease in parallel resistance (increased leakage current) and an increase in minority carrier recombination current. For vacuum-processed absorber layers, this thermal effect is still within an acceptable range; however, for solution-processed CIGS, the damage is significantly aggravated.

[0006] On the other hand, in the scribing integration process of thin-film solar cell modules, the third scribing (P3) was initially performed using mechanical scribing (scraping away the top electrode layer with a hard blade). Conventional mechanical P3 scribing has significant drawbacks: the blade tip width is much larger than the laser focusing spot, resulting in a wide scribing groove (60-80 μm); simultaneously, to avoid damage to the adjacent P2 interconnect channels due to blade vibration, P3 must maintain a large safety distance from P2. The large area between P2 and P3, where both the top and bottom electrodes are interrupted, cannot effectively collect photogenerated carriers and occupies valuable light-receiving area, forming a so-called "dead zone," severely limiting the module's short-circuit current density. Therefore, laser scribing P3 technology has been gradually developed in this field, utilizing the small (approximately 10 μm) and non-contact processing characteristics of the laser focusing spot to effectively reduce the dead zone area. However, laser scribing is a thermal processing procedure, and the heat-affected zone it creates on the copper indium gallium selenide (CIGS) absorber layer may lead to local elemental volatilization and phase segregation, leaving room for optimization in large-area modules. Summary of the Invention

[0007] The purpose of this invention is to address the two technical challenges mentioned in the background above. This invention provides a solution-based copper indium gallium sulfide thin-film solar cell module and its fabrication method based on ultraviolet-green light synergistic scribing. For scribing P1 and P2, a 355 nm ultraviolet laser with high photon energy and low thermal diffusion is used to achieve low thermal damage scribing by primarily using a photochemical bond breaking mechanism. For scribing P3, a 532 nm green laser is used instead of mechanical scribing. By utilizing the non-contact characteristics and micron-level focusing precision of the laser, the P3 channel width is widened, and the scribing is cleaner with less residue.

[0008] Technical Solution: This invention provides a solution-based copper indium gallium sulfide (CIGS) thin-film solar cell module based on UV-green light synergistic scribing, comprising a substrate and functional film layers. The substrate is molybdenum-coated soda-lime glass. The functional film layers, from the substrate upwards, are a molybdenum back electrode layer, a silver-doped CIGS light-absorbing layer, a cadmium sulfide (CdS) buffer layer, an intrinsic zinc oxide high-resistivity window layer, and a transparent conductive oxide low-resistivity window layer. The module has three scribing lines. The first scribing line (P1) cuts through the molybdenum back electrode layer to isolate the back electrodes of adjacent sub-cells. The second scribing line (P2) pierces through the intrinsic zinc oxide high-resistivity window layer, the CdS layer, and the CIGS light-absorbing layer, and fills with transparent conductive oxide to form a series interconnection channel between the front and rear electrodes of the sub-cells. The third scribing line (P3) pierces through the transparent conductive oxide low-resistivity window layer, the intrinsic zinc oxide, the CdS buffer layer, and the CIGS light-absorbing layer to achieve electrical separation of the top electrodes of adjacent sub-cells. The P1 and P2 scribing lines are executed at a wavelength of 355 nm. The P3 lines are formed by ultraviolet laser scribing with a wavelength of 532 nm, while the P3 lines are formed by green laser scribing with a wavelength of 532 nm.

[0009] Preferably, the transparent conductive oxide low-resistivity window layer is indium tin oxide (ITO) with a thickness of 350 nm; the silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer has an Ag atomic percentage of 5%; and the intrinsic zinc oxide high-resistivity window layer has a thickness of 50 nm.

[0010] Preferably, the component comprises 6 sub-cells connected in series; the number of sub-cells is determined by the number of back electrode strips divided by vertical lines P1, and the total open-circuit voltage of the component is the sum of the open-circuit voltages of each sub-cell.

[0011] Preferably, the groove width of the six vertical P1 lines of the six series-connected sub-cells is 50 μm, of which the width of the two parallel edge clearing lines is 90 μm, the distance between the P2 line and the vertical P1 line on the same side is 50 μm, the groove width of the P2 line is 60 μm, the distance between the P3 line and the P2 line on the same side is 40 μm, and the total width of the invalid area occupied by the three lines P1 / P2 / P3 in a single sub-cell is 250 μm.

[0012] The present invention also provides a method for preparing the solar cell module as described above, comprising the following steps:

[0013] (1) P1 scribing: Take a molybdenum-plated sodium-calcium glass substrate and scribing the molybdenum layer according to the design pattern with a pulsed ultraviolet laser with a wavelength of 355 nm to form a strip-shaped back electrode area that is electrically isolated from each other. After scribing, the resistance between adjacent back electrodes is not less than 100 MΩ.

[0014] (2) Preparation of silver-doped copper indium gallium sulfide (CIGS) light absorption layer: On the substrate with P1 scribing completed, a precursor film was coated by spin coating-pre-annealing cycle using an N,N-dimethylformamide (DMF) precursor solution containing Cu, In, Ga, Ag metal sources and sulfur source. Then, high-temperature sulfurization crystallization was carried out in a sulfur-containing atmosphere to obtain the CIGS light absorption layer.

[0015] (3) Preparation of cadmium sulfide (CdS) buffer layer: CdS thin film was deposited on the CIGS light absorption layer by chemical bath deposition;

[0016] (4) Preparation of intrinsic zinc oxide high-resistivity window layer: i-ZnO thin film was deposited on CdS buffer layer by magnetron sputtering;

[0017] (5) P2 scribing: Using a pulsed ultraviolet laser with a wavelength of 355 nm, scribing is performed along the side of the P1 scribing line. The scribing depth reaches at least to the surface of the Mo back electrode to form an interconnect channel that penetrates the i-ZnO / CdS / CIGS stack. After scribing, the contact resistance between the bottom of the channel and the Mo layer is not higher than 2 Ω.

[0018] (6) Preparation of transparent conductive oxide low-resistivity window layer: a transparent conductive oxide thin film is deposited all over the cell by magnetron sputtering. The thin film fills the P2 channel at the same time, so that the top electrode of the sub-cell is electrically connected to the back electrode of the adjacent sub-cell through the channel.

[0019] (7) P3 scribing: Using a pulsed green laser with a wavelength of 532 nm, scribing is performed along the side of P2 away from P1 by a predetermined distance to remove the transparent conductive oxide low-resistivity window layer, the intrinsic zinc oxide high-resistivity window layer, the CdS buffer layer, and the CIGS light absorption layer, thereby separating the top electrodes of adjacent sub-cells.

[0020] (8) Electrode lead-out: Remove the transparent conductive oxide low-resistivity window layer, intrinsic zinc oxide high-resistivity window layer, CdS buffer layer, and CIGS light absorption layer at the beginning and end of the series battery array to expose the Mo layer, and fabricate positive and negative collectors to obtain the solar cell module.

[0021] Preferably, in step (2), the specific method for preparing the silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer includes the following steps:

[0022] (1) Dissolve copper salt, indium salt, gallium salt and silver salt in DMF in proportion, add thiourea as sulfur source and ligand, and stir until completely dissolved to obtain molecular precursor solution;

[0023] (2) Spin-coat the precursor solution onto the substrate at a speed of 3000 rpm, and anneal it on a hot plate at 340°C for 1 minute after spin coating. Repeat the spin coating-annealing process 10 times.

[0024] (3) Place the spin-coated sample in a graphite box and put it into a tube furnace. Under a sulfur vapor atmosphere, perform sulfur crystallization treatment at 680°C for 30 minutes. After natural cooling, the CIGS light absorption layer is obtained.

[0025] Preferably, both the ultraviolet laser and the green laser in the method are picosecond pulsed lasers; the laser power for P1 scribing is selected as the lowest power value that can penetrate the Mo layer without significantly damaging the glass substrate; P2 scribing adopts a two-step power strategy, first using high power to groove down to the Mo layer, and then using low power to clean and scan the bottom of the groove to remove residual interface layer and molten debris; P1 scribing uses an ultraviolet laser at a frequency of 200 kHz, a power of 2.5 W, and a wavelength of 1000 mm / s. -1 The P2 scribing was performed at a scanning speed of 200 kHz, 1 W, and 1000 mm / s. -1 The parameters were then used for a second scan along the same trajectory, with parameters of 200 kHz, 0.5 W, and 1000 mms. -1 The parameters.

[0026] Preferably, in step (7), the laser power of the green laser P3 scribing is the lowest power value that is just enough to remove the ITO / i-ZnO / CdS / CIGS light absorption layer without significantly damaging the underlying Mo layer. The P3 scribing uses 200 kHz, 0.56 W, and 1000 mm / s. -1 The parameters.

[0027] The present invention also provides an application of the solar cell module as described above in power supply of low-power electronic devices, wherein the open-circuit voltage of the solar cell module is not less than 5 V under the standard test conditions of AM 1.5G, 100 mW / cm².

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. This invention uses a 355 nm ultraviolet laser to scribing P1 and P2, which can effectively reduce thermal damage during the scribing process and improve the back electrode isolation quality and sub-cell interconnection quality.

[0030] 2. This invention uses a 532 nm green laser to complete the P3 scribing, which has the advantages of non-contact processing, high processing accuracy and good repeatability, and can effectively reduce the dead area of ​​the component and increase the effective light-receiving area of ​​the component.

[0031] 3. This invention proposes a differentiated scribing process that uses ultraviolet laser for P1 and P2 and green laser for P3, achieving synergistic optimization of low thermal damage processing and high-precision scribing, improving the module fill factor and photoelectric conversion efficiency, and reducing the performance loss from cell to module.

[0032] 4. The process of this invention is simple and suitable for large-area monolithic integration fabrication of copper indium gallium sulfide thin-film solar cells using the solution method, and has good prospects for industrial application. Attached Figure Description

[0033] Figure 1 A schematic diagram of the overall structure of the copper indium gallium sulfide solar cell prepared according to the present invention;

[0034] Figure 2 This is a flowchart illustrating the overall preparation process of the present invention;

[0035] Figure 3 Here is a schematic diagram of the P1 marking process; where a is the top view of P1 before marking, b is the cross-sectional view of P1 before marking, c is the top view of P1 after marking, and d is the cross-sectional view of P1 after marking.

[0036] Figure 4 Here is a schematic diagram of the P2 scribing process; where a is the top view before the P2 scribing process, b is the cross-sectional view before the P2 scribing process, c is the top view after the P2 scribing process, and d is the cross-sectional view after the P2 scribing process.

[0037] Figure 5 Here is a schematic diagram of the P3 scribing process; where a is the top view before the P3 scribing process, b is the cross-sectional view before the P3 scribing process, c is the top view after the P3 scribing process, and d is the cross-sectional view after the P3 scribing process.

[0038] Figure 6 This is a schematic diagram of the edge-cleaning line marking; where a is a schematic diagram before the edge-cleaning line marking, and b is a schematic diagram after the edge-cleaning line marking.

[0039] Figure 7 A three-dimensional schematic diagram of a copper indium gallium sulfide (CIGS) solar cell module.

[0040] Figure 8 The images show a comparison of SEM images after P1 green laser and P1 ultraviolet laser scribing; where a is the SEM image after P1 green laser scribing and b is the SEM image after P1 ultraviolet laser scribing.

[0041] Figure 9 The images show SEM images after P2 green laser and P2 ultraviolet laser scribing, where a is the SEM image after P2 green laser scribing and b is the SEM image after P2 ultraviolet laser scribing.

[0042] Figure 10 The images show a comparison of SEM images after P3 mechanical scribing and P3 green laser scribing, where a is the SEM image after P3 mechanical scribing and b is the SEM image after P3 green laser scribing.

[0043] Figure 11 This is a photograph of the finished product of the first scribing method for the six-section components in this invention;

[0044] Figure 12 This is a photograph of the finished product of the second scribing method for the six-section components in this invention;

[0045] Figure 13 This is a comparison chart of the performance (JV) of different scribing methods in this invention;

[0046] Figure 14 This is a JV curve diagram of a single cell before series connection provided in this invention. Detailed Implementation

[0047] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, modifications, or variations made to the present invention by those skilled in the art without departing from the spirit and substance of the invention should fall within the scope of protection of the present invention.

[0049] The molybdenum-coated soda-lime glass used in this invention is a commercially available product, with a molybdenum metal thickness between 1000 nm. The DMF, metal salts, and other chemical reagents used in this invention are all commercially available analytical grade products.

[0050] Example 1

[0051] This embodiment illustrates the structure and fabrication process of copper indium gallium sulfide thin-film solar cell modules processed using the solution method. Figure 1 and Figure 2 As shown.

[0052] This embodiment provides a large-area copper indium gallium sulfide (CIGS) thin-film solar cell module and its preferred preparation method.

[0053] Step 1: The back electrode is scribed onto a molybdenum (Mo)-coated soda-lime glass (SLG) substrate using a picosecond laser with a wavelength of 355 nm; this step is called P1. Before scribing... Figure 3 As shown in a and b, the engraved pattern is as follows Figure 3 As shown in c and d, the scribing depth must ensure that the Mo layer is completely etched to form an electrically isolated back electrode pattern.

[0054] Step 2: Preparation of silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer. A CIGS light-absorbing layer is prepared on the substrate after P1 scribing using a solution method. Specifically, copper, indium, and gallium metal salts are dissolved in an organic solvent with a sulfur source in a specific ratio to form a precursor solution. This solution is then spin-coated, dried at low temperature, and sulfided at 680°C to form a CIGS polycrystalline thin film with a thickness of approximately 1–1.5 μm.

[0055] Step 3: Prepare a cadmium sulfide buffer layer and an intrinsic zinc oxide high-resistivity window layer on the CIGS light-absorbing layer;

[0056] Step 4: In such Figure 4 The films shown in a and b are arranged as follows Figure 4 The scribing patterns shown in c and d are used to scribing the thin film, which is called P2. P2 scribing requires the complete removal of the intrinsic zinc oxide high-resistivity window layer, cadmium sulfide buffer layer, and absorber layer on Mo.

[0057] Step 5: After P2 is scribing, an ITO window layer is sputtered onto the thin film using vacuum sputtering, thus connecting the top and bottom electrodes of adjacent cells. The sputtering conditions are: gas pressure 0.4 Pa, sputtering power 80 W, and module film thickness 350 nm.

[0058] Step Six: In such Figure 5 The films shown in a and b are arranged as follows Figure 5The scribing patterns shown in c and d are laser scribing, which is called P3. In this invention, the P3 line scribing removes all the ITO, high-resistivity window layer, cadmium sulfide buffer layer and absorption layer on Mo, with the aim of completely separating the top electrodes of adjacent cells.

[0059] Step Seven: In such Figure 6 The film shown in Figure a is arranged as follows Figure 6 The edge-cleaning pattern shown in Figure b is created by using a blade to remove the ITO, high-resistivity window layer, cadmium sulfide buffer layer, and absorber layer from the SLG. The final product is a copper indium gallium sulfide (CIGS) module, with the overall module structure as shown below. Figure 7 As shown. Figure 7 This is a three-dimensional structural diagram of the monolithically integrated solar cell module of the present invention. From bottom to top, the solar cell module includes a glass substrate, a Mo back electrode layer, a CIGS light-absorbing layer, a CdS buffer layer, an i-ZnO high-resistivity window layer, and an ITO transparent conductive layer. Multiple sub-cells are connected in series by scribing P1, P2, and P3. Scribing P1 penetrates the Mo back electrode layer, achieving isolation between the back electrodes of adjacent sub-cells; scribing P2 removes the absorption layer, CdS buffer layer, and i-ZnO high-resistivity window layer above the Mo back electrode, exposing the Mo back electrode and providing a contact area for electrical connection between adjacent sub-cells; scribing P3 removes the ITO transparent conductive layer, insulating the front electrodes of adjacent sub-cells from each other and preventing short circuits. Through these three scribing steps, multiple sub-cells are integrated in series, thereby improving the module's output voltage.

[0060] Example 2

[0061] This embodiment is used to illustrate P1 picosecond laser marking:

[0062] A 4 cm × 4 cm soda-lime glass (SLG) substrate coated with molybdenum (Mo) is taken, with a molybdenum layer thickness of approximately 1000 nm. First, the substrate is laser-scribed. Two horizontal lines, the widest of which are the edge cleaning lines, are 90 μm wide, and six vertical lines are designated as P1 lines, each 50 μm wide. The molybdenum conductive layer is then scribed according to the designed pattern to achieve electrical isolation of the molybdenum back contact. After scriber work, the Mo layer is applied to both ends of P1, with the scribe depth just covering the molybdenum layer (approximately 900-1000 nm). Using a multimeter, the resistance at both ends of the scribe line should be greater than 100 MΩ, and the line depth should be between 900-1200 nm.

[0063] Example 3

[0064] This embodiment illustrates the setup for fabricating a copper indium gallium sulfide absorber layer on a molybdenum conductive layer:

[0065] A molecular precursor solution based on N,N-dimethylformamide (DMF) containing copper, indium, gallium, and silver salts (Ag content 5%) was prepared by mixing 2.435 g thiourea (TU), 1.407 g InCl3·4H2O, 0.36 g GaCl3, 0.60 g CuCl, and 0.046 g AgCl in 10 mL of DMF. The resulting mixture was stirred vigorously for 6 hours, followed by standing for 2 hours to ensure complete dissolution and equilibrium.

[0066] The substrate was immersed in ethanol for 20 minutes, followed by ultrasonic cleaning. The ethanol was then replaced with deionized water, and ultrasonic cleaning continued to ensure thorough removal of surface contaminants. The substrate was then dried with a nitrogen stream. Next, 0.37 mL of the precursor solution was dotted onto a molybdenum-coated soda-lime glass substrate in air, with spin-coating parameters of 3000 rpm and 30 seconds. After spin-coating, the sample was placed on a hot plate for pre-annealing (340°C, 1 minute 30 seconds). The spin-coating-annealing process was repeated multiple times (approximately 10 times) to obtain the desired precursor film thickness.

[0067] The sample with the precursor film deposited was placed in a graphite reaction chamber and subjected to high-temperature sulfidation treatment in a sulfur-containing atmosphere at a temperature of 680°C for 30 minutes. After the treatment, the sample was allowed to cool naturally to room temperature to obtain the CIGS light-absorbing layer.

[0068] Example 4

[0069] This embodiment illustrates the setup for fabricating a cadmium sulfide buffer layer on a copper indium gallium sulfide absorber layer:

[0070] A cadmium sulfide buffer layer was deposited on the CIGS light-absorbing layer using chemical bath deposition (CBD). The specific steps were as follows: 225 ml of ultrapure water was placed in a jacketed beaker, and the sample was fixed in place using a mold before being placed inside; 30 ml of a 1.65 mmol / L CdSO4 aqueous solution and 40 ml of ammonia water were added, stirred, and 65°C hot water was passed through; after 1 minute, 30 ml of a 0.825 mol / L thiourea aqueous solution was added, and deposition was allowed to proceed for 12 minutes; finally, the sample surface was rinsed with deionized water to remove adsorbed cadmium sulfide particles, and the sample was dried using a nitrogen gun.

[0071] Example 5

[0072] This embodiment illustrates the setup for preparing an intrinsic zinc oxide window layer on a cadmium sulfide buffer layer:

[0073] An intrinsic zinc oxide (i-ZnO) high-resistivity window layer was prepared on top of a CdS buffer layer by magnetron sputtering at an argon atmosphere and a pressure of 0.4 Pa. The sputtering power was 80 W and the film thickness was approximately 50 nm after 8 min of sputtering.

[0074] Example 6

[0075] This embodiment is used to illustrate P2 picosecond laser marking:

[0076] On the i-ZnO deposited film, a line with a width of 60 μm is scribed approximately 50 μm away from the P1 line on one side, using a picosecond laser for P2 scribe. A two-step scribe method is preferred for P2 scribe: the first step uses high power for initial scribe, scribes the line down to the Mo layer; the second step uses reduced power to clean the scribed line, removing residual molten metal and the interface layer, i.e., cutting through the i-ZnO window layer, CdS buffer layer, and CIGS light-absorbing layer, creating a channel connecting the top and bottom electrodes of adjacent cells. A probe station is used to test the resistance between the scribe line and the bottom molybdenum layer to confirm the interconnect quality.

[0077] Example 7

[0078] This embodiment is used to illustrate the parameters of P3 green laser scribing:

[0079] P3 lines were scribing performed on the ITO-deposited thin film using a 532 nm green laser to delineate the top electrodes according to the design, separating the top electrodes of adjacent cells. Following the design, lines were scribed approximately 40 μm away from the P2 line on one side of the P1 and P2 lines, with a line width of 50 μm. P3 laser scribing offers significant advantages over traditional mechanical scribing: mechanical scribing often results in edge chipping and debris generation, while laser scribing achieves high precision and clean scribing. Furthermore, the superior edge quality and higher scribing precision of laser scribing effectively suppress edge chipping and residual conductive debris, increasing the fairing (FF) from 43% to 52%.

[0080] Example 8

[0081] This embodiment is used to illustrate the method of marking the edge line:

[0082] When marking P1, a total of eight lines are marked: six vertical P1 lines and two horizontal edge-cleaning lines. After marking P3, a blade is used to mark the marking channels of the original horizontal edge-cleaning lines to remove all ITO / i-ZnO / CdS / CIGS above the two channels. The purpose is to prevent the top electrode and the back electrode from short-circuiting.

[0083] Example 9

[0084] This embodiment illustrates the method for preparing battery electrodes:

[0085] After completing the P3 scribing, use a blade to scrape out molybdenum to the left of the leftmost P3 line and to the right of the rightmost P3 line; be careful not to touch the P3 line, and then plate indium in the scraped molybdenum area to obtain the positive and negative electrodes.

[0086] Method for determining positive and negative terminals: Draw a line from P1 to P2, and determine its adjacent interconnecting line P2. Along the direction perpendicular to the two lines, the side pointing from P1 to P2 is defined as the current converging direction, and the corresponding end is the negative terminal of the component; the other end is the positive terminal of the component.

[0087] Example 10

[0088] This embodiment is used to illustrate the comparative effects of solar cell modules fabricated by P1 using green laser and ultraviolet laser scribing, respectively:

[0089] The substrate and functional film preparation steps of the two sets of solar cell modules are consistent with the complete process flow of Example 1, and the preferred process parameters described in Examples 2 to 9 are used to complete the preparation. The difference lies in the P1 scribing process. Specifically, the P1 parameters for green light are frequency 200 kHz, power 2.1W, and movement speed 1000 mm / s, while the P1 parameters for ultraviolet light are frequency 200 kHz, power 2.5W, and movement speed 1000 mm / s. Figure 8 SEM comparison images of P1 green laser and P1 ultraviolet laser scribing, as shown. Figure 8 As shown in Figure a, after green laser scribing, obvious burrs and molten material redeposition appeared at the edge of the P1 trench, with a large amount of conductive residue; as shown in Figure a. Figure 8 As shown in b, after UV laser scribing, the P1 trench is clean and smooth, with almost no molten material redeposition and conductive residue.

[0090] The multimeter test results show that the isolation resistance of the ultraviolet laser P1 scribe line is about 160 MΩ, which is much higher than the green laser's about 50 MΩ, indicating that the electrical isolation effect of the molybdenum back contact is significantly improved.

[0091] Example 11

[0092] This embodiment is used to illustrate the comparative effects of solar cell modules fabricated by P2 using green laser and ultraviolet laser scribing, respectively:

[0093] The substrate and functional film preparation steps for both sets of solar cell modules were consistent with the complete process flow of Example 1, and the preferred process parameters described in Examples 2-9 were used for preparation. Line P1 used the UV scribing parameters from Example 10. The difference lay in the scribing process for P2. For the green laser P2, the parameters were 200 kHz, 0.84 W, and 1000 mm / s. Subsequently, the power was reduced to 0.35 W on the original scribing channel for a second cleaning. For the UV P2, the scribing parameters were 200 kHz, 1 W, and a movement speed of 1000 mm / s. A second scan was then performed along the same trajectory, with parameters of 200 kHz, 0.5 W, and 1000 mm / s, scribing the line to molybdenum. After UV P2 scribing, the interconnect resistance was 1.5 Ω, significantly lower than the approximately 8 Ω of the green laser scribing. The advantages of P2 ultraviolet laser scribing are: the higher energy and lower thermal diffusion of ultraviolet photons help to remove the absorption layer more efficiently, and the electrical contact between the transparent conductive oxide and the Mo back electrode is significantly improved. Figure 9 SEM images of P2 green laser and P2 ultraviolet laser scribing, as shown. Figure 9 As shown in a and b, it can be concluded that compared with green laser scribing, ultraviolet laser processing exhibits clearer scribing edges, less thermal damage, and less re-coagulation debris, resulting in better performance.

[0094] Example 12

[0095] This embodiment is used to illustrate the comparative effects of solar cell modules prepared by P3 using mechanical scribing and green laser scribing, respectively:

[0096] The preparation steps of the substrate and functional film layer of the two sets of solar cell modules are consistent with the complete process flow of Example 1, and the preferred process parameters described in Examples 2 to 9 are used to complete the preparation. The P1 line adopts the ultraviolet scribing parameters in Example 10, and the P2 line adopts the ultraviolet scribing parameters in Example 11. The difference lies in the scribing process of P3. Specifically, the P3 line is patterned by mechanical scribing and 532 nm green laser scribing, respectively. Figure 10 SEM comparison images of P3 green laser and P3 ultraviolet laser scribing, as shown. Figure 10 As shown in a and b, after mechanical scribing, the scribing edge shows cracks and debris; while after green laser scribing, the edge is smooth and without cracks.

[0097] Example 13

[0098] This embodiment illustrates the preferred schemes for solar cell modules fabricated by P3 using mechanical scribing and green laser scribing, respectively:

[0099] Method 1: The preparation steps for the substrates and functional films of both sets of solar cell modules are consistent with the complete process flow of Example 1, and the preferred process parameters described in Examples 2-6 and 8-9 are used for preparation. P1 uses the UV scribing parameters in Example 10; P2 uses the UV scribing parameters in Example 11. The difference lies in the scribing process of P3, which uses mechanical scribing. The actual image after scribing is shown below. Figure 11 As shown. Figure 13 As shown, the component FF obtained by scribing method one is approximately 43.51%, and Jsc is 2.22 mA / cm².

[0100] Method 2: The preparation steps for the substrates and functional films of both sets of solar cell modules are consistent with the complete process flow of Example 1, and the preparation is completed using the preferred process parameters described in Examples 2-9. The difference lies in the scribing process for P3. Specifically, P1 uses a 355 nm ultraviolet laser for scribing; P2 uses a 355 nm ultraviolet laser for scribing; and P3 uses a 532 nm green laser for scribing. The actual images after scribing are shown below. Figure 12 As shown. Figure 13 As shown, the six-section series assembly obtained using scribing method two exhibits the best overall performance: PCE of 6.52%, Voc of 5.18 V, Jsc of 2.38 mA / cm², FF of 52.87%, P1 isolation resistance of 160 MΩ, and P2 interconnection resistance of 1.5 Ω. This method fully leverages the comprehensive advantages of laser in scribing accuracy, edge quality, and low thermal damage, resulting in superior overall performance compared to method one.

[0101] Two different scribing methods were employed: scribing lines P1 and P2 were both done using 355 nm ultraviolet laser, while line P3 was scribed using 532 nm green light. This process was considered the optimal solution. Laser scribing has irreplaceable advantages in solution-processed CIGS module fabrication, and the cell-to-module (CTM) voltage loss of this invention is less than 1%, indicating that voltage loss during module integration is negligible. For heat-sensitive material systems like solution-processed CIGS absorber layers, the low thermal diffusion characteristics of ultraviolet lasers are particularly crucial.

[0102] Example 14

[0103] This embodiment is used to compare the electrical performance of a series-connected module with that of a single battery cell:

[0104] The electrical performance of the six-cell series assembly prepared by scribing method two in Example 13 was compared with that of a single-cell battery prepared simultaneously. Figure 14As shown, the Voc of a single battery cell is 0.87 V, while in Example 13, the Voc of the six-cell series assembly (method two) is 5.18 V, approximately six times that of a single battery cell (5.18 / 0.87≈5.95), consistent with the voltage multiplication rule of series circuits. This indicates that the voltage loss during series integration is extremely small.

[0105] The FF (efficiency factor) of a single cell is 62.70%, and that of the module is 52.87%. The decrease in FF is mainly due to the increase in series resistance and the existence of the P2 / P3 dead zone, with an FF loss of approximately 16%. The Jsc (efficiency per square meter) of the module (14.27 mA / cm² based on effective area) and the Jsc of a single cell (15.41 mA / cm²) are about 7.39% lower, demonstrating the advantage of laser scribing with narrow dead zones. The overall PCE (process efficiency) loss is approximately 22.47%. In this invention, ultraviolet laser scribing is preferably used for processes P1 and P2. Compared to green laser, ultraviolet laser can achieve higher precision material removal, reduce the heat-affected zone and re-solidified debris, thereby obtaining better interface quality.

Claims

1. A solution-based copper indium gallium sulfide thin-film solar cell module based on ultraviolet-green light synergistic marking, comprising a substrate and a functional film layer, characterized in that, The substrate is molybdenum-plated sodium-calcium glass. The functional film layers, from the substrate upwards, are a molybdenum back electrode layer, a silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer, a cadmium sulfide (CdS) buffer layer, an intrinsic zinc oxide high-resistivity window layer, and a transparent conductive oxide low-resistivity window layer. The component has three scribing lines. The first scribing line (P1) cuts through the molybdenum back electrode layer to isolate the back electrodes of adjacent sub-cells. The second scribing line (P2) cuts through the intrinsic zinc oxide high-resistivity window layer, the CdS layer, and the CIGS light-absorbing layer and fills the transparent conductive oxide to form a series interconnection channel between the front and rear electrodes of the sub-cells. The third scribing line (P3) cuts through the transparent conductive oxide low-resistivity window layer, the intrinsic zinc oxide, the CdS buffer layer, and the CIGS light-absorbing layer to achieve electrical separation of the top electrodes of adjacent sub-cells. The P1 and P2 scribing lines are formed using a 355 nm ultraviolet laser, and the P3 scribing line is formed using a 532 nm green laser.

2. The solution-based copper indium gallium sulfide thin-film solar cell module based on ultraviolet-green light synergistic marking according to claim 1, characterized in that, The transparent conductive oxide low-resistivity window layer is indium tin oxide (ITO) with a thickness of 350 nm; the silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer has an Ag atomic percentage of 5%; and the intrinsic zinc oxide high-resistivity window layer has a thickness of 50 nm.

3. The solution-based copper indium gallium sulfide thin-film solar cell module based on ultraviolet-green light synergistic marking according to claim 1, characterized in that, The component comprises 6 sub-cells connected in series; the number of sub-cells is determined by the number of back electrode strips divided by vertical lines P1, and the total open-circuit voltage of the component is the sum of the open-circuit voltages of each sub-cell.

4. The solution-based copper indium gallium sulfide thin-film solar cell module based on ultraviolet-green light synergistic marking according to claim 1, characterized in that, The groove width of the six vertical P1 lines in the six series-connected sub-cells is 50 μm, of which the two parallel edge clearing lines are 90 μm wide. The distance between the P2 line and the vertical P1 line on the same side is 50 μm, the groove width of the P2 line is 60 μm, and the distance between the P3 line and the P2 line on the same side is 40 μm. The total width of the invalid area occupied by the three lines P1 / P2 / P3 in a single sub-cell is 250 μm.

5. The method for preparing a solar cell module as described in claim 1, characterized in that, Includes the following steps: (1) P1 scribing: Take a molybdenum-plated sodium-calcium glass substrate and scribing the molybdenum layer according to the design pattern with a pulsed ultraviolet laser with a wavelength of 355 nm to form a strip-shaped back electrode area that is electrically isolated from each other. After scribing, the resistance between adjacent back electrodes is not less than 100 MΩ; (2) Preparation of silver-doped copper indium gallium sulfide (CIGS) light absorption layer: On the substrate with completed P1 scribing, the precursor film is coated by spin coating-pre-annealing cycle with an N,N-dimethylformamide (DMF) precursor solution containing Cu, In, Ga, Ag metal sources and sulfur source. Then, high-temperature sulfurization crystallization is carried out in a sulfur-containing atmosphere to obtain the CIGS light absorption layer; (3) Preparation of cadmium sulfide (CdS) buffer layer: CdS thin film was deposited on the CIGS light absorption layer by chemical bath deposition; (4) Preparation of intrinsic zinc oxide high-resistivity window layer: i-ZnO thin film was deposited on CdS buffer layer by magnetron sputtering; (5) P2 scribing: Using a pulsed ultraviolet laser with a wavelength of 355 nm, scribing is performed along the side of the P1 scribing line. The scribing depth reaches at least to the surface of the Mo back electrode to form an interconnect channel that penetrates the i-ZnO / CdS / CIGS stack. After scribing, the contact resistance between the bottom of the channel and the Mo layer is not higher than 2 Ω. (6) Preparation of transparent conductive oxide low-resistivity window layer: a transparent conductive oxide thin film is deposited all over the cell by magnetron sputtering. The thin film fills the P2 channel at the same time, so that the top electrode of the sub-cell is electrically connected to the back electrode of the adjacent sub-cell through the channel. (7) P3 scribing: Using a pulsed green laser with a wavelength of 532 nm, scribing is performed along the side of P2 away from P1 by a predetermined distance to remove the transparent conductive oxide low-resistivity window layer, the intrinsic zinc oxide high-resistivity window layer, the CdS buffer layer, and the CIGS light absorption layer, thereby separating the top electrodes of adjacent sub-cells. (8) Electrode lead-out: Remove the transparent conductive oxide low-resistivity window layer, intrinsic zinc oxide high-resistivity window layer, CdS buffer layer, and CIGS light absorption layer at the beginning and end of the series battery array to expose the Mo layer, and fabricate positive and negative collectors to obtain the solar cell module.

6. The method for preparing a solar cell module according to claim 5, characterized in that, In step (2), the specific method for preparing the silver-doped copper indium gallium sulfide (CIGS) light-absorbing layer includes the following steps: (1) Dissolve copper salt, indium salt, gallium salt and silver salt in DMF in proportion, add thiourea as sulfur source and ligand, and stir until completely dissolved to obtain molecular precursor solution; (2) Spin-coat the precursor solution onto the substrate at a speed of 3000 rpm, and anneal it on a hot plate at 340°C for 1 minute after spin coating. Repeat the spin coating-annealing process 10 times. (3) Place the spin-coated sample in a graphite box and put it into a tube furnace. Under a sulfur vapor atmosphere, perform sulfur crystallization treatment at 680°C for 30 minutes. After natural cooling, the CIGS light absorption layer is obtained.

7. The method for preparing a solar cell module according to claim 5, characterized in that, In this method, both the ultraviolet laser and the green laser are picosecond pulsed lasers; the laser power for P1 scribing is selected as the lowest power value that can penetrate the Mo layer without significantly damaging the glass substrate; P2 scribing adopts a two-step power strategy: first, high power is used to groove down to the Mo layer, and then low power is used to clean and scan the bottom of the groove to remove residual interface layer and molten debris; P1 scribing uses ultraviolet light at a frequency of 200kHz, a power of 2.5W, and a wavelength of 1000mm / s. -1 The P2 scribing was performed at a scanning speed of 200 kHz, 1 W, and 1000 mm / s. -1 The parameters were then used for a second scan along the same trajectory, with parameters of 200 kHz, 0.5 W, and 1000 mms. -1 The parameters.

8. The method for preparing a solar cell module according to claim 5, characterized in that, In step (7), the laser power of the green laser P3 scribing is the lowest power value that is just enough to remove the ITO / i-ZnO / CdS / CIGS light absorption layer without significantly damaging the underlying Mo layer. The P3 scribing uses 200 kHz, 0.56 W, and 1000 mm / s. -1 The parameters.

9. The application of the solar cell module as described in any one of claims 1-8 in power supply for low-power electronic devices, characterized in that, Under the standard test conditions of AM 1.5G and 100 mW / cm², the open-circuit voltage of the solar cell module is not less than 5 V.